KONSEP ADIL DAN AMANAH DALAM PEMBERANTASAN KORUPSI MENURUT HUKUM ISLAM - yoga vandita, Lalu; Yogi Mandala Putra, Lalu (Universitas Nahdlatul Ulama Al Ghazali Cilacap, 2025)
Corruption is an injustice, whether for personal enrichment, for the enrichment of a group, or for a class. Corruption is a violation of a given mandate and violates the values ​​of justice. Islamic law expressly prohibits betraying a mandate or ignoring the values ​​of justice in everyday life. The method used in this study is a library search by analyzing sources such as books, journals, articles, legal documents, and other written sources. This allows the researcher to draw conclusions. There is a need to instill the values ​​of justice in society. Justice in law is crucial not only because the law must be just, but because justice is more important than the law